Level of nutrition knowledge personal trainer in West java - Apriantono, Tommy; Hasan, Fahmi; Bahri, Samsul; Bahana, Irianti; Rahadian, Raden Aswin; Hasan, Muhamad Fahmi (Universitas Nusantara PGRI Kediri, 2021)
Personal Trainer (PT) has a significant role in educating the community, including Nutrition Knowledge (NK). However, not all PT has a good NK. This research was conducted to determine how many PT with good NK are material for stakeholder evaluation to raise the level of Nutrition Knowledge in the broader community. Research is undertaken with survey methods, a type of quantitative descriptive. The study subjects were obtained by purposive sampling technique, obtaining 187 samples. To get NK, used Body Composition, Metabolism, and Dietary Requirements Questionnaire, there are 21 questions adapted from previous research. Furthermore, the data is obtained from the results of questionnaires that have been filled out independently by the subject through a google form. The results of research data are processed statistically using SPPS version 25. The subjects consisted of 187 participants with an average age of 27 years. The results showed that the study subjects' NK was in poor condition based on statistical test results. The level of NK that has not been optimal in the PT environment is a significant concern for improving competence and support to maximize NK to improve the Indonesian people's degree of health. The results of this study can be a suggestion and evaluation for policy stakeholders because there need to be improvements from policies that encourage the emergence of NK increases in the PT.